Adverse reaction to nicotine gum in malay female smoker: a case report - Noorzurani, M.H.R.; Bond, A.; Wolff, K. (2008)
Nicotine replacement therapies (NRT) are prescribed in smoking cessation programmes to help smokers stop smoking. The ideal dosage of NRT should control cravings and withdrawal symptoms but avoid adverse reactions. This report describes a case of adverse reaction to nicotine gum in a female Malay smoker. Assays taken 2 h after the gum, showed that her plasma cotinine/nicotine ratio was 0.4, indicating poor nicotine metabolic status. She developed nausea, severe vomiting and diarrhoea with raised blood pressure and pulse rate, following the administration of a piece of 2 mg nicotine gum on an empty stomach. This was observed in the course of a study to determine nicotine metabolism. Nicotine gum may be associated with adverse reactions in those with poor nicotine metabolic rate. Further investigation is required into the clinical effects of nicotine gum in those with poor nicotine metabolic status.